PROCEDURE FOR T-TUBE CHOLANGIOGRAPHY IN PATIENTS WITH CLINICAL CHOLANGITIS AT THE RADIOLOGY UNIT OF RSAB PEKANBARU - M. Syawal Syahputra; Muhammad Habib Irfan; Rona Faradila (Medical Imaging and Radiation Protection Research Journal, 2025)
Background: T-tube cholangiography is a radiographic examination of the biliary system that uses a positive contrast medium injected through a T-tube catheter to evaluate biliary tract patency and detect residual stones, strictures, or postoperative complications. In clinical practice, examination procedures may vary among hospitals, particularly regarding the imaging modality and radiographic projections employed. Therefore, evaluating the examination procedure is essential to improve the quality of radiology services. Objective: This study aimed to describe the T-tube cholangiography procedure performed in a patient with clinical cholangitis at the Radiology Unit of RSAB Pekanbaru and to compare the procedure with established radiographic theories and literature. Methods: This study employed a descriptive qualitative approach using a case study design involving one patient diagnosed with cholangitis. Data were collected through direct observation, documentation, and a review of the examination procedure, including patient preparation, contrast media administration, radiographic techniques, and image evaluation. Results: The examination was performed using a conventional digital radiography (DR) X-ray system with a water-soluble iodinated contrast medium. The radiographic projections included a preliminary anteroposterior (AP) view, a post-contrast AP view, and a right posterior oblique (RPO) projection. The findings demonstrated opacification of the hepatobiliary system, multiple filling defects within the common bile duct (CBD), and passage of contrast into the duodenum without evidence of complete obstruction, indicating multiple choledocholithiasis.